Efficiency measurement of the English football Premier League with a random frontier model - Barros, Carlos Pestana; Garcia-del-Barrio, Pedro (Economic modelling, 2008)
Using the random stochastic frontier model, this paper examines the technical efficiency of the English football Premier League from 1998/99 to 2003/04. The model disentangles homogenous and heterogeneous variables in the cost function, which leads us to advise the implementation of common policies as well as policies by clusters.